Regional Disparities in Public Expenditure Effectiveness; A Comparative Analysis of Western and Eastern Indonesia - Sabir, Sabir; Rahman R, Abd; Fernandes, Adji Achmad Rinaldo; Bakar, Normizan bin (Economics Department, Faculty of Economic and Islamic Business, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study investigates the impact of government expenditure on employment across Indonesia’s regional economies, incorporating private investment as a mediating variable and region as a moderating variable. Using data from 2010 to 2022, the analysis focuses on five categories of government spending: general, housing and settlement, economic, education, and health. A multigroup path analysis model is employed to examine both direct and indirect effects of these expenditures on employment. The results reveal that government spending has a stronger impact on employment in the western region compared to the eastern region. Regional differences significantly moderate the relationship between government expenditure and private investment, particularly in general, economic, education, and health spending. In contrast, housing and settlement expenditure consistently affect both regions. Furthermore, private investment significantly enhances employment, especially in the western provinces. These findings underscore the importance of accounting for regional disparities in fiscal policy design and provide valuable insights for developing more effective and equitable regional economic strategies in Indonesia.